Cohort study of growth patterns by gestational age in preterm infants developing morbidity. Issue 11 (17th November 2016) - Klevebro, S; Lundgren, P; Hammar, U; Smith, L E; Bottai, M; Domellöf, M; Löfqvist, C; Hallberg, B; Hellström, A
Abstract : Objectives: To examine differences in growth patterns in preterm infants developing major morbidities including retinopathy of prematurity (ROP), bronchopulmonary dysplasia (BPD), necrotising enterocolitis (NEC) and intraventricular haemorrhage (IVH). Study design: Cohort study of 2521 infants born at a gestational age (GA) of 23–30 weeks from 11 level III neonatal intensive care units in USA and Canada, and 3 Swedish population-based cohorts. Outcomes: Birth weight and postnatal weight gain were examined relative to birth GA and ROP, BPD, NEC and IVH development. Results: Among infants with a birth GA of 25–30 weeks, birth weight SD score and postnatal weight were lower in those developing ROP and BPD. Infants developing ROP showed lower growth rates during postnatal weeks 7–9 in the 23–24 weeks GA group, during weeks 4–6 in the 25–26 weeks GA group and during weeks 1–5 in the 27–30 weeks GA group. Infants with BPD born at 27–30 weeks GA showed lower growth rates during postnatal weeks 3–5. Infants with NEC had lower growth rates after postnatal week 6 in all GA groups, with no significant differences in birth weight SD score. IVH was not associated with prenatal or postnatal growth. Conclusions: In this cohort study of extremely preterm infants, we found that the postnatal growth pattern was associated with morbidities such as ROP, BPD and NEC as well as with gestational age at birth.